High Salt Intake Augments Excitability of PVN Neurons in Rats: Role of the Endoplasmic Reticulum Ca2+ Store - Larson, Robert A.; Chapp, Andrew D.; Gui, Le; Huber, Michael J.; Cheng, Zixi Jack; Shan, Zhiying; Chen, Qing-Hui (Frontiers in Neuroscience, 2017)
High salt (HS) intake sensitizes central autonomic circuitry leading to sympathoexcitation. However, its underlying mechanisms are not fully understood. We hypothesized that inhibition of PVN endoplasmic reticulum (ER) Ca2+ store function would augment PVN neuronal excitability and sympathetic nerve activity (SNA). We further hypothesized that a 2% (NaCl) HS diet for 5 weeks would reduce ER Ca2+ store function and increase excitability of PVN neurons with axon projections to the rostral ventrolateral medulla (PVN-RVLM) identified by retrograde label. PVN microinjection of the ER Ca2+ ATPase inhibitor thapsigargin (TG) increased SNA and mean arterial pressure (MAP) in a dose-dependent manner in rats with a normal salt (NS) diet (0.4%NaCl). In contrast, sympathoexcitatory responses to PVN TG were significantly (p<0.05) blunted in HS treated rats compared to NS treatment. In whole cell current-clamp recordings from PVN-RVLM neurons, graded current injections evoked graded increases in spike frequency. Maximum discharge was significantly augmented (p<0.05) by HS diet compared to NS group. Bath application of TG (0.5 µM) increased excitability of PVN-RVLM neurons in NS (p<0.05), yet had no significant effect in HS rats. Our data indicate that HS intake augments excitability of PVN-RVLM neurons. Inhibition of the ER Ca2+-ATPase and depletion of Ca2+ store likely plays a role in increasing PVN neuronal excitability, which may underlie the mechanisms of sympathoexcitation in rats with chronic HS intake.